The determinants of international migration in early modern Europe: Evidence from the maritime sector, c. 1700-1800 - Alexander Klein; Jelle Van Lottum (University of Kent, School of Economics, 2017)
This paper offers the first multivariate regression study of international migration in early modern Europe. Using unique eighteenth-century data about maritime workers, we created a data set of migration flows among European countries to examine the role of factors related to geography, population, language, the market and chain migration in explaining the migration of these workers across countries. We show that among all factors considered in our multivariate analysis, the geographical characteristics of the destination countries, size of port towns, and chain migration are among the most robust and quantitatively the most important factors influencing cross-country migration flows.
Keywords: F22; F63; 330; international migration; economic development